Molecular Identification Confirms Different Species of Cotton Jassids (Hemiptera: Cicadellidae) in Tanzania - Joseph Elias Nyesse; Gration Mutashoberwa Rwegasira; Luseko Amos Chilagane (Journal of Tropical Crop Science, 2026)
Cotton (Gossypium hirsutum L.) is a strategic  cash crop in Tanzania, supporting the livelihoods of approximately two million people and contributing substantially to the national agricultural economy through lint production and the textile industry. However, cotton productivity is severely constrained by sap-sucking insect pests, particularly cotton jassids (Hemiptera: Cicadellidae), which can cause yield losses of up to 50%. Pest management strategies have largely been implemented with limited knowledge of the actual species composition of jassids infesting cotton fields. This study aimed to establish the molecular identity of cotton-associated sucking pests, with an emphasis on jassids, in major cotton-growing areas of Tanzania. A total of 25 specimens were collected from cotton fields in Bunda, Meatu, Misungwi, and Kilosa districts. Genomic DNA was extracted using the Quick- DNA™ Mini Prep Plus Kit, and the mitochondrial cytochrome oxidase subunit I (COI) gene was amplified using COI 1-3b and COI 2-4b primer pairs. PCR amplicons were visualized on 1.2% agarose gels, and successfully amplified products were sequenced. Approximately 650-bp COI sequences were analyzed using Maximum Likelihood methods implemented in MEGA v.12 and aligned with global reference datasets to infer phylogenetic relationships. Phylogenetic reconstruction resolved well-supported clades representing Amrasca, Jacobiasca, Ghauriana, and Empoasca species. Most specimens clustered strongly with authenticated reference sequences of Amrasca biguttula (bootstrap support 92–100%), confirming its presence as a dominant cotton pest. Additional samples grouped with Jacobiasca lybica, Jacobiasca formosana, Ghauriana sinensis, Empoasca distinguenda, and E. flavescens. Findings reveal considerable species diversity among cotton jassids in Tanzania and underscore the importance of integrating molecular diagnostics into routine pest surveillance to support species-specific and sustainable integrated pest management strategies.